Orthodontic management in a female patient with an impacted incisor in the mandible – case report - Świątkowska, Agnieszka; Dunin-Wilczyńska, Izabella; Świątkowski, Wojciech (Forum Ortodontyczne / Orthodontic Forum, 2018)
Traumas to deciduous teeth, such as intrusion and complete avulsion, lead to the most severe injuries to tooth buds of permanent teeth. The most common post-traumatic complications of permanent teeth include: enamel hypoplasia or hypocalcification, crown or root dilaceration, partial or complete inhibition of root growth, and eruption disorders. Aim. The paper aimed to present orthodontic treatment in a female patient with an impacted permanent lower incisor with significantly impaired morphology due to a trauma to its deciduous predecessor. Material. Material included: patient’s orthodontic records, gypsum models, photographs and radiological records. Results. Orthodontic treatment was successful despite abnormal morphology of the impacted tooth 41. After 4-year follow-up the tooth remains in the arch. Conclusions. A tooth can be preserved in the socket when the crown-to-root ratio (CRR) is at least 1 : 1. In this case, CRR for the tooth 41 was 2 : 1, and therefore its extraction would be recommended. Despite this a decision was made to introduce an impacted tooth into the arch. Thanks to its presence in the dental arch it was possible to preserve appropriate bone quality for implantation of a prosthetic implant in the future. Prosthetic treatment (if necessary) may be performed after completion of vertical growth of the face that is observed in women after the age of 16 years. Summary. This case of a 15-year female patient shows that as a result of orthodontic and surgical intervention and despite significant root shortening the tooth may remain in the dental arch and play its functional and aesthetic role. (Świątkowska A, Dunin-Wilczyńska I, Świątkowski W. Orthodontic management in a female patient with an impacted incisor in the mandible – case report. Orthod Forum 2018; 14: 150-7).